Analisis Strategi Inovasi UMKM Berbasis Kearifan Lokal (Studi Pada UMKM Di Kabupaten Jombang Jawa Timur) - Cahyo Tri Atmojo (IKIP Budi Utomo Malang, 2023)
The research that we have done aims to find out the innovation strategy based on local wisdom that has been carried out by UMKM Kunara. The method that we have used is descriptive qualitative method. The data collection that researchers have done is through observation, while the observation method is systematic observation and recording of the objects we have examined. Researchers used the guided free interview technique. In conducting interviews, the system carried out by researchers is by observing the location of UMKM Kunara in Dsn. Melik Ds. Kedungrejo Kec. Megaluh Kab. Jomabang. For data collection techniques, the researcher compiled various series of questions that had been prepared. The authors submitted them to the informants (owners and employees). From the interview results, it was found that the business being run by Kunara was already in the growth stage. This situation made Kunara more enthusiastic about carrying out the business strategy that had been implemented. The business strategy that has been implemented by Kunara includes the 4Ps (Product, Price, Place, and Promotion). The implementation of this strategy is expected to be able to develop Kunara's business to be better in the future.